CAPTURING STUDENTS ENGLISH LEARNING EXPERIENCES THROUGH PHOTOVOICE - Berita Mambarasi Nehe; Yulinar Rahayu Fahmi; Nunung Nurhayati (STBA LIA - Jakarta, 2022)
This research aimed to find out the experiences of students in learning English online during COVID-19 and students’ writing skills. It uses Photovoice as the research methodology. Data collection is done through Photovoice and in-depth interviews. 15 students of class VIII-I of SMPN 1 Rangkasbitung participated in this study. Data from students' explanations on their photos were analyzed qualitatively to find out students' experiences of learning English online through their writings about the photos. After that, the researcher did a cross check and compared the information from the students' writings, photos and interviews. In this study, researchers found that the Photovoice method can be used as a technique to help students in learning English. It can also help students express their experience of learning English online during the pandemic. Besides that, students' perception of English learning online during the pandemic has negative perceptions. This can be shown from the results of Photovoice supported by in-depth interviews. 11 out of 15 students got negative feelings, while four students had positive feelings. Three students stated they have difficulty in joining online classes and 12 students stated the other way around. From the findings above, it can be concluded that the Photovoice method can be used for teaching writing as students can still learn online easily.